A Healthy Beverage Score and Risk of Chronic Kidney Disease Progression, Incident Cardiovascular Disease, and All-Cause Mortality in the Chronic Renal Insufficiency Cohort. Issue 6 (21st May 2020) - Hu, Emily A; Anderson, Cheryl A M; Crews, Deidra C; Mills, Katherine T; He, Jiang; Shou, Haochang; Taliercio, Jonathon J; Mohanty, Madhumita J; Bhat, Zeenat; Coresh, Josef; Appel, Lawrence J; Rebholz, Casey M; et al.
ABSTRACT: Background: Beverages are a source of calories and other bioactive constituents but are an understudied aspect of the diet. Different beverages have varying effects on health outcomes. Objectives: We created the Healthy Beverage Score (HBS) to characterize participants' beverage patterns and examined its association with chronic kidney disease (CKD) progression, incident cardiovascular disease (CVD), and all-cause mortality among individuals with CKD. Methods: We conducted a prospective analysis of 2283 adults aged 21–74 y with a baseline estimated glomerular filtration rate of 20–70 mL · min −1 · 1.73 m −2 from the Chronic Renal Insufficiency Cohort. Diet was assessed using a 124-item FFQ at visit 1 (2003–2008). The HBS, ranging from 7 to 28 possible points, consisted of 7 components, each scored from 1 to 4 based on rank distribution by quartile, except alcohol, which was based on sex-specific cutoffs. Participants were given more points for higher consumption of low-fat milk and of coffee/tea, for moderate alcohol, and for lower consumption of 100% fruit juice, whole-fat milk, artificially sweetened beverages, and sugar-sweetened beverages. CKD progression, incident CVD, and mortality were ascertained through January 2018. We conducted multivariable Cox proportional hazards models. Results: There were 815 cases of CKD progression, 285 cases of incident CVD, and 725 deaths over a maximum of 14 y of follow-up. Compared with participants in the lowest tertile of the HBS, participants in the highest tertile had a 25% lower likelihood of CKD progression (HR: 0.75; 95% CI: 0.63, 0.89; P -trend = 0.001) and a 17% lower likelihood of all-cause mortality (HR: 0.83; 95% CI: 0.69, 1.00; P -trend = 0.04) after adjusting for sociodemographic, clinical, and dietary factors. There was no significant trend for incident CVD. Conclusions: Among individuals with CKD, a healthier beverage pattern was inversely associated with CKD progression and all-cause mortality. Beverage intake may be an important modifiable target in preventing adverse outcomes for individuals with CKD.